Gharar in Shafi'i Jurisprudence: Reassessing Its Validity in E-CommerceTransactions - Arum Indiharwati; Mailah; Nor Asiah Binti Mohamad (University of Darusssalam Gontor, 2025)
The widespread adoption of e-commerce among Muslim consumers presents significant legal challenges, particularly concerning the validity of digital transactions under Shafi’i jurisprudence, which emphasizes contractual clarity and certainty. This researchaddresses these challenges by reassessing the concept of ghararwithin the Shafi’i school in modern digital commerce. It sets out three objectives,to examine classical definitions and legal thresholds of ghararaccording to Shafi’i scholars,identify manifestations of uncertainty in current e-commerce practices,andevaluate the extent to which reinterpretation is possible while maintaining doctrinal consistency. Using a normative juridical method and content analysis of classical texts such as Mukhtashar Al-Ummand Al-Majmu’, as well as contemporary scholarship, thisresearchfinds that most digital transaction uncertainties qualify as ghararyasir (minor uncertainty) and therefore do not invalidate contracts. These findings underscore that consumer consent, established commercial customs (‘urf), and platform safeguards(such as refund policies and transparency features) effectively reduce legal ambiguity. The research further confirms that the Shafi’i framework possesses sufficient flexibility, through legal maxims (qawaid fiqhiyyah) and considerations of public interest (maslahah), to accommodate evolving transaction models without compromising its core principles. Thus, thisresearchaffirms the ongoing relevance of Shafi’i jurisprudence in regulating the ethical and legal dimensions of e-commerce.